(untitled) (Journal of Plant Disease Sciences, 2017)
Soil samples collected from different locations exhibited 9 isolates of two genera capable of degrading chitin on colloidal chitin agar media. Based on morphological and cultural characteristics isolates were categorised as four of Aspergillus niger Aspergillus flavus (AN1 to AN4) and five of (AF1 to AF5). All the isolates were found effective against Fusarium udum, Rhizoctonia bataticola Sclerotium rolfsii, and confirmed by dual culture technique. The isolate AN3 of from Chandur and AF4 of from Aspergillus niger Aspergillus flavus Borgaon exhibited maximum antagonistic activity against inhibiting the F. udum pathogen by 84.28 and 87.63, per cent respectively. was inhibited by R. bataticola 69.62 and 82.07 per cent respectively by AN3 and AF5. In case of , AN3 S. rolfsii and AF5 exhibited maximum percent growth inhibition . 69.61and 81.05 percent i.e respectively. Fungicide Carboxin + Thiram and Thiram alone inhibited the growth of by approximately 90% in all isolates isolates were inhibited by A.niger . A.flavus 100% due to Carboxin + Thiram and Carbendazim. Overall insecticides and weedicides were less toxic to all the isolates compared to fungicides.